PENGARUH RETURN ON ASSET, CURRENT RATIO, DAN DEBT TO ASSET RATIO TERHADAP FINANCIAL DISTRESS PADA PT LEYAND INTERNATIONAL Tbk PERIODE 2014-2023 - Pangaribuan, Hasudungan; Agusentoso, Randhy; Dwianggoro, Prihadi; Octavianti, Santi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effect of Return On Asset, Current Ratio, and Debt to Asset Ratioon financial distress at PT Leyand International Tbk during the 2014-2023 period. The method used in this research is a quantitative associative approach with secondary data obtained from the company's annual financial statements for 10 years. Data analysis was performed using multiple linear regression with the help of the SPSS25 program. T test results show that Return On Asset (0,041<0,05) and Debt to Asset Ratio (0,036<0,05) have a significant effect on financial distress. Conversely, Current Ratio (0,461>0,05have no significant effect on financial distress. Meanwhile, the f test results show that Return On Asset, Current Ratio, and Debt to Asset Ratio together have a significant effect on financial distress with a significance value of 0.006 with a coefficient of determination (R²) of 0,825 or 82,5%. Thus, it can be concluded that although not all independent variables have a partial effect, the four financial ratios simultaneously have an influence on the company's financial distress condition.